Risk based feeding protocol in ICU - Chittawatanarat, Kaweesak (Indonesian Nutrition Association, 2024)
A risk-based feeding regimen in the ICU aims for optimal nutritional support by customizing feeding methods to the particular risk attributes of critically ill patients. These are the key components and concepts of this strategy. 1) Risk stratification: This includes the risk of malnutrition and feeding complications. 2) Feeding Initiation: For patients at high nutritional risk or with severe illness, early enteral nutrition (EN) including trophic feeding should begin within 24-48 hours after ICU admission.